Characterization of Alternaria polianthi causing leaf blight disease intuberose and standardization of its growth parameters - Sonavane, P; Poojitha, S R; Bharathi, T U; Nandeesha, P; Azeez, S; Kumar, R; Venugopalan, R; Dhananjaya, M V; Tejaswini, P (Journal of Horticultural Sciences, 2026)
Tuberose is an ornamental crop cultivated for its long-lasting spikes and alluring scent. The incidence of leaf blight disease caused by Alternaria polianthi is the most widespread and severe, resulting in reduced growth and significant yield losses. In the present study, a pure culture was isolated from the infected leaves of tuberose and based on typical symptoms on the foliage, microscopic observation and cultural traits of the fungus, it was identified as Alternaria polianthi, which was further confirmed by molecular characterization showing 100% similarity with Alternaria sp. infecting only tuberose host. Ten different media were tested to analyze the growth parameters, among them the mean colony diameter was found highest on corn meal agar (9 cm), potato dextrose agar (8.80 cm), potato carrot agar (8.27 cm) and other colony parameters were greatly influenced by the type of the growth media. Excellent sporulation was observed on corn meal agar, potato dextrose agar and water agar. This is the first kind of study on molecular characterization of Alternaria polianthi on tuberose in India.